The Evaluation of Invasive Fungal Infections in Patients with Hematological Malignancy - Aydın, Selda; Mert, Ali; Öztürk, Recep (Cerrahpaşa Medical Journal, 2025)
Objective: Invasive fungal infections (IFIs) are a major complication in patients with hematological malignancies, leading to significant morbidity and mortality. This study aimed to evaluate the epidemiological, clinical, and microbiological perspective of IFIs in febrile neutropenic patients with hematologic malignancies. Methods: This prospective study was conducted in the hematology unit of a 1709-bed university hospital between April 2008 and December 2010. Among 727 hospitalized patients with hematological malignancies, 168 febrile neutropenic patients with suspected IFIs were followed during the study period. Diagnostic evaluation included blood cultures, galactomannan antigen testing, high-resolution computed tomography, respiratory tract, and other sampling. Samples were evaluated as microbiological and pathological in terms of IFI. Results: Hundred out of 168 patients (59.5%, n = 100/168) were diagnosed with IFIs, corresponding to an incidence of 13.8%. Mold infections predominated (86%, n = 86/100), with invasive pulmonary aspergillosis accounting for the majority of cases, while candidemia represented the leading cause of proven infections (76.4%, n = 13/17). Less common pathogens included Fusarium spp., Trichosporon spp., and Pneumocystis jirovecii. The overall 30-day mortality rate was 54%, with the highest case fatality observed in probable and proven IPA. Conclusion: This study highlights the substantial burden and high mortality associated with IFIs in patients with hematological malignancies during the 2008-2010 period, prior to widespread antifungal prophylaxis and advanced diagnostics. Despite recent progress leading to lower incidence and improved survival, IFIs remain a critical clinical challenge. Early diagnosis and optimized antifungal strategies are essential to improving outcomes in this patient population. Cite this article as: Aydın S, Mert A, Öztürk R. The evaluation of invasive fungal infections in patients with hematological malignancy. Cerrahpaşa Med J. 2025, 49, 0080, doi: 10.5152/cjm.2025.25080.